Evaluation of tbe Intensity Distribution by Image Processing - Mohammed, A.A.; Jabur, R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Image processing is an important source for the image analytical in order to get variable parameters such as the intensity .In present work it has been found a relation between the tensity and number of pixd in the image , and from this relation we have got in this paper the intensity di:s tribution in the photo picture. One of the an important sources of image is t he remote sensing technique. The development relation that we have got is a numerical analysis added to the remote sensing field .